High-Sensitive Acoustic Sensor Based on Microfiber Mach–Zehnder Interferometer with Tapered Polarization-Maintaining Fiber. Issue 1 (4th March 2022) - Zhu, Xiaojun; Liu, Wen; Sun, Dan; Zhang, Guoan; Zou, Li; Liang, Zhipeng; Han, Zhanghua; Shi, Yuechun
ABSTRACT: We propose a high sensitive acoustic sensor based on a microfiber Mach-Zehnder interferometer (MMZI) with tapered polarization-maintaining fiber (PMF). The optical tapering technology is used to taper the PMF. Then, the MMZI is attached to a wood pulp diaphragm (WPD) to form an acoustic sensor, whose curvature will change with the vibration of the diaphragm. Two sensors with different waist diameters are made for performance comparison. Experimental results show that the acoustic sensor can achieve a wideband frequency response range from 200 Hz to 4000 Hz. The responses are flat at frequencies ranging from 200 Hz to 1500 Hz. Moreover, we find that the sensing performance of the acoustic sensor improves with the decrease in its waist diameter. When the waist diameter is 25.72 μm, the response sensitivity of the sensor can reach 42.4 mV/kPa at 2000 Hz, and the minimum detection pressure is 1.24 Pa/√Hz. It provides an effective way to fabricate an acoustic sensor, with low cost, easy integration, and high sensitivity.